Processing User Input in Tracking Problems using Model Predictive Control. Issue 1 (July 2017) - Knauer, M.; Büskens, C.
Abstract: Using the application of a container crane in a high rack warehouse, the problem class of tracking problems is introduced, where the system has to reach a possible time dependent reference value while maintaining stability and safety. These problems are a subclass of nonlinear model predictive control problems, and can be solved numerically as optimal control problems. Numerical results are given for the described application, as well as some considerations on reducing the computational time.